Direct antiviral agent treatment of chronic hepatitis C results in rapid regression of transient elastography and fibrosis markers fibrosis‐4 score and aspartate aminotransferase‐platelet ratio index. (3rd November 2016) - Bachofner, Jacqueline A.; Valli, Piero V.; Kröger, Arne; Bergamin, Irina; Künzler, Patrizia; Baserga, Adriana; Braun, Dominique; Seifert, Burkhardt; Moncsek, Anja; Fehr, Jan; Semela, David; Magenta, Lorenzo; et al.
Abstract: Background: Novel direct antiviral agents (DAA) targeting hepatitis C virus (HCV) have revolutionized the treatment of chronic hepatitis C infection (CHC). Rates of sustained virological response (SVR) to treatment have drastically improved since introduction of DAA. Transient Elastography (TE) is an ultrasound based, non‐invasive technique to assess liver stiffness (LS). We examined the changes in TE values and fibrosis scores FIB‐4 and APRI after DAA treatment of CHC. Methods: 549 patients who received a DAA based treatment for CHC were screened and 392 were included. TE values recorded prior to therapy and within 18 months after therapy were evaluated. In addition, FIB‐4 and APRI scores were calculated and histopathological results were recorded if available. Results: Median TE prior to DAA treatment was 12.65 kPa (IQR 9.45‐19.2 kPa) and decreased to 8.55 kPa (IQR 5.93‐15.25) post‐treatment. This finding is statistically significant ( P <.001) and equals a TE regression of 32.4% after DAA treatment. Median FIB‐4 and APRI values significantly decreased from 2.54 (IQR 1.65‐4.43) and 1.10 (IQR 0.65‐2.43) to 1.80 (IQR 1.23‐2.84, P <.001) and 0.43 (IQR 0.3‐0.79, P <.001) respectively. Conclusion: Patients with SVR after DAA therapy showed significant regression of TE values. Rapid decrease in TE was in concordance with regression of validated fibrosis scores FIB‐4 and APRI. It remains to be examined whether this indicates a true regression of fibrosis or merely resolution of chronic liver inflammation with subsequent improvement of TE values and laboratory parameters.